Pengaruh Pengetahuan, Manfaat, Risiko Dan Kepercayaan Investasi Terhadap Minat Investasi Mahasiswa Pada Saham Syariah - Putri, Ethika Kirana; Fifianawati, Fifianawati; Wahadah, Tri Nur; Damayanti, Alfinda; Aulia R, Diva Meizahra; Ayudiati, Citra (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
Shariah stock investment is still of the highest interest on the IDX to developing assets productively. However, there are still many obstacles to be faced. The purpose of this study was to know about influence knowledge, benefits, risks and trust on interest in investing in Islamic stocks within the scope of students at Cokroaminoto University, Yogyakarta. The method used is a quantitative approach using a survey method of UCY students as a research sample and data collected through a questionnaire. The results of the research that has been done are that there is a significant influence on the variable of trust in the interest in investing in Islamic stocks while the influence of benefits, knowledge, and risks do not have a significant effect on the interest in investing in Islamic stocks during UCY student.